The effects of HPMC concentration as an efficient pharmaceutical dosage form on phage release pattern from gels - Meysam Adibi; Ava Soltani Hekmat; Nazanin Mobasher; Younes Ghasemi; Milad Mohkam; Shima Jafari; Mohammad Ali Mobasher (Shiraz University of Medical Sciences, 2017)
Bacteriophages (phages) are natural particles to deal with bacteria. The resistance of bacteria to various antibiotics has accelerated in recent years and phages can be used for each particular strain. The best way to deal with superficial infections is topical application of the drug. One of the best way is the use of water-based gels such as hydroxy propyl methyl cellulose (HPMC). In addition to sustain drug release properties of the gel base, HPMC itself has healing properties. The final composition of the gel should has property lasting right time on the woundwhile release a number of the appropriate phages per unit of time. After Isolation and purification of phage, it has been trapped into HPMC gel. Gels with different concentrationsused to create plaques and show the release rate of the phage gel. Finally, it was shown that the 2% HPMC has most appropriate pharmaceutical features In terms of the release and durability on the site of infection.